Technique in overarm throwing - Nurhidayah Omar (2016)
A computer simulation model of overarm throwing was developed to gain an understanding of the mechanics of overarm throwing and applied to fastball pitching. The movement was modelled as a three-dimensional system using eight rigid segments, with torque generators for upper trunk extension/flexion, upper trunk external/internal rotation, scapula external/internal rotation, right upper arm flexion/extension, right upper arm adduction/abduction and right upper arm external/internal rotation. The baseball was attached at the distal end of the hand segment using a linear spring. The model was personalised to a pitcher so that simulation outputs could be compared with the pitcher s performance. Kinematic data of overarm pitching were obtained using a Vicon Motion Analysis System and maximal voluntary joint torques were estimated using average maximal voluntary joint torques from previous studies. A torque-driven model was used to determine a specific set of maximal voluntary joint torques by varying T_o while matching three performances concurrently. The torque-driven model was successfully evaluated, and shown to produce realistic movements, with mean overall differences between simulations and performances of 13% for three trials. The model was applied to further the understanding of the mechanics of overarm throwing. Optimising the technique of the pitcher with the simulation model increased the ball speed by 14% with more upper trunk flexion, scapula internal rotation and right upper arm external rotation used. The optimised technique showed proximal-to-distal sequencing, and increasing strength by 5% gave a slight improvement in performance of 0.6%. Varying strength by ±30% resulted in an increase of 2.7% in ball speed although not all joints used the 30% increase in strength. In summary, although increasing strength resulted in an increase in ball speed, technique variables such as upper trunk flexion and upper arm external rotation are arguably the most important factors for throwing fast.